Upward ballooning of the third ventricle floor in a patient with slit ventricle syndrome: A unique magnetic resonance imaging finding - Yamaguchi, Junya (Neuroradiol J, 2016)
Slit ventricle syndrome (SVS) is a well-known chronic complication of ventriculoperitoneal shunt (VPS) placement. In this report, we describe a unique anatomical change that we observed on the magnetic resonance (MR) images of the brain acquired from a patient with SVS. The patient was a 40-year-old woman who had undergone VPS placement at 3 months of age. A computed tomography scan of her brain revealed a slit-like ventricle. In addition, an MR image of her brain revealed upward ballooning of the third ventricle floor, which returned to normal after a lumbar puncture. This anatomical change resulted from the pressure gradient between the intra- and extraventricular spaces. We believe our findings will further our understanding of the pathogenesis of SVS. Moreover, we hope our findings will help clinicians to select endoscopic third ventriculostomy as the primary surgical approach in patients with this particular SVS pathogenesis in order to avoid complications.